2018
DOI: 10.1080/2162402x.2018.1509820
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PD-L1 expression across breast cancer molecular subtypes, in relation to mutation rate, BRCA1-like status, tumor-infiltrating immune cells and survival

Abstract: To better understand the expression pattern of programmed death-ligand 1 (PD-L1) expression in different breast cancer types, we characterized PD-L1 expression in tumor and tumor-infiltrating immune cells, in relation to mutation rate, BRCA1-like status and survival. We analyzed 410 primary treatment-naive breast tumors comprising 162 estrogen receptor-positive (ER+) and HER2−, 101 HER2+ and 147 triple-negative (TN) cancers. Pathologists quantified tumor-infiltrating lymphocytes (TILs) and PD-L1 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
92
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 58 publications
15
92
4
4
Order By: Relevance
“…We report, to our knowledge for the first time, a significant association between BRCA1 promoter hypermethylation and PD-L1 expression, in both tumor and immune cells. In the study by Sobral-Leite et al, PD-L1 expression showed a modest but significant positive association with the number of silent mutations in TNBC [71]. However, PD-L1 was not associated with BRCA1-like status evaluated using multiplex ligation-dependent probe amplification, an assay unable to identify methylation status.…”
Section: Discussionmentioning
confidence: 94%
“…We report, to our knowledge for the first time, a significant association between BRCA1 promoter hypermethylation and PD-L1 expression, in both tumor and immune cells. In the study by Sobral-Leite et al, PD-L1 expression showed a modest but significant positive association with the number of silent mutations in TNBC [71]. However, PD-L1 was not associated with BRCA1-like status evaluated using multiplex ligation-dependent probe amplification, an assay unable to identify methylation status.…”
Section: Discussionmentioning
confidence: 94%
“…Details on data management and patient selection were described previously . Survival data, estrogen receptor (ER) status, progesterone receptor (PR) status are updated since the previous publication on TSR according to the last publication using the ONCOPOOL study …”
Section: Methodsmentioning
confidence: 99%
“…14,34 Survival data, estrogen receptor (ER) status, progesterone receptor (PR) status are updated since the previous publication on TSR according to the last publication using the ONCOPOOL study. 14,35 All patient data were used in an anonymized manner and data were handled according to national ethical guidelines ("Code for Proper Secondary Use of Human Tissue", Dutch Federation of Medical Scientific Societies"). No additional informed consent was required.…”
Section: Study Populationmentioning
confidence: 99%
“…First, PD‐L1 IHC expression was evaluated in TMAs (with duplicate cores from each tumor) rather than in whole‐tissue sections. Previous studies in BC showed that TMA protein assessment underestimated PD‐L1 expression due to its spatial heterogeneity as compared to whole‐tissue sections (Sobral‐Leite et al , 2018). Moreover, SP263 clone was used for PD‐L1 IHC, which should be put into the context of low reported analytical concordance among different antibodies in BC (Rugo et al , 2019).…”
Section: Discussionmentioning
confidence: 99%